Non-reactive and reactive block copolymers for toughening of UV-cured epoxy coating - Naguib, Mohamed; Sangermano, Marco; Capozzi, Luigi C.; Pospiech, Doris; Sahre, Karin; Jehnichen, Dieter; Scheibner, Holger; Voit, Brigitte (Progress in Organic Coatings, 2015)
Reactive and non-reactive diblock copolymers based on polyethylene oxide (PEO) and a poly(glycidyl methacrylate) (PGMA, reactive) or polystyrene (non-reactive) block, respectively, are prepared via ATRP and those are incorporated into a cycloaliphatic epoxy matrix. Crosslinking of the matrix is then performed by cationic UV curing, producing modified thermosets. 1H NMR and SEC measurements are carried out and used to analyze the composition, the molar mass and dispersity of the prepared block copolymers. The viscoelastic properties and morphology of the modified epoxy are determined using DMTA and FESEM, respectively. The addition of 4 and 8 wt% of the reactive PEO-b-PGMA block copolymer into epoxy resin has only minor effects on the glass transition temperature, Tg. The reactive homopolymer PGMA significantly increases and the non-reactive block copolymer PEO-b-PS slightly decreases the glass transition temperature of the epoxy matrix. The non-reactive block copolymer PEO-b-PS causes a little decrease in Tg values. The measurement of the critical stress factor, KIC, shows that the fracture toughness of the composite materials is enhanced by inclusion of the non-reactive block copolymer. In contrary, the reactive block copolymer has negative effect on the fracture toughness especially in case of short PEO block. FESEM micrographs studies on the fracture surfaces sustain the microphase separation and the increase in surface roughness in the toughened samples, indicating more energy was dissipated.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Block copolymers; Epoxy resin; Toughening; UV-curing